Peroxisome Proliferator-activated Receptor-α-mediated Transcription of miR-199a2 Attenuates Endothelin-1 Expression via Hypoxia-inducible Factor-1α - Li, Chen; Mpollo, Marthe-Sandrine Eiymo Mwa; Gonsalves, Caryn S.; Tahara, Stanley M.; Malik, Punam; Kalra, Vijay K. (The Journal of biological chemistry, 2014)
Endothelin-1, a potent vasoconstrictor, plays an important role in pulmonary hypertension (PH) in sickle cell disease (SCD). Our previous studies show that higher levels of placenta growth factor (PlGF), secreted by erythroid precursor cells, correlate with increased plasma levels of endothelin-1 (ET-1) and other functional markers of PH in SCD. PlGF-mediated ET-1 expression occurs via activation of hypoxia-inducible factor-1α (HIF-1α). However, relatively less is understood regarding how PlGF-mediated expression of HIF-1α and its downstream effector ET-1 are post-transcriptionally regulated. Herein, we show that PlGF treatment of endothelial cells resulted in reduced levels of miR-199a2, which targeted the 3′-UTR of HIF-1α mRNA and concomitantly led to augmented ET-1 expression. Plasma levels of miR-199a2 in SCD subjects were significantly lower with reciprocally high levels of plasma ET-1, unlike unaffected controls. This observation provided a molecular link between miR-199a2 and high levels of ET-1 in SCD. Furthermore, we show that miR-199a2 located in the DNM3os transcription unit was co-transcriptionally regulated by peroxisome proliferator-activated receptor α (PPARα). Binding of the latter to PPARα cis-elements in the promoter of DNM3os was demonstrated by promoter mutational analysis and ChIP. Additionally, we show that fenofibrate, a PPARα agonist, increased the expression of miR-199a2 and DNM3os; the former was responsible for reduced expression of HIF-1α and ET-1. In vivo studies of fenofibrate-fed Berkeley sickle mice resulted in increased levels of miR-199a2 and reduced levels of ET-1 in lung tissues. Our studies provide a potential therapeutic approach whereby fenofibrate-induced miR-199a2 expression can ameliorate PH by reduction of ET-1 levels.Elevated plasma levels of PlGF are associated with increased endothelin-1 and pulmonary hypertension (PH) in SCD. miR-199a2, which targets HIF-1α mRNA, located in host gene DNM3os is co-transcriptionally regulated by PPARα. PPARα agonist induction of miR-199a2 reduced ET-1 levels. PPARα agonist reduction of ET-1 levels via induced miR-199a2 provides an alternative strategy to ameliorate PH.